lncRNA GAS6-AS1 inhibits progression and glucose metabolism reprogramming in LUAD via repressing E2F1-mediated transcription of GLUT1 - Jing Luo; Huishan Wang; Li Wang; Gaoming Wang; Yu Yao; Kai Xie; Xiaokun Li; Lin Xu; Yi Shen; Binhui Ren (Molecular Therapy: Nucleic Acids, 2021)
Glucose metabolism reprogramming is one of the hallmarks of cancer cells, although functional and regulatory mechanisms of long noncoding RNA (lncRNA) in the contribution of glucose metabolism in lung adenocarcinoma (LUAD) remain incompletely understood. The aim of this study was to uncover the role of GAS6-AS1 in the regulation of progression and glucose metabolism in LUAD. We discovered that overexpression of GAS6-AS1 suppressed tumor progression of LUAD both in vitro and in vivo. Metabolism-related assays revealed that GAS6-AS1 inhibited glucose metabolism reprogramming. Mechanically, GAS6-AS1 was found to repress the expression of glucose transporter GLUT1, a key regulator of glucose metabolism. Ectopic expression of GLUT1 restored the inhibition effect of GAS6-AS1 on cancer progression and glucose metabolism reprogramming. Further investigation identified that GAS6-AS1 directly interacted with transcription factor E2F1 and suppressed E2F1-mediated transcription of GLUT1, and GAS6-AS1 was downregulated in LUAD tissues and correlated with clinicopathological characteristics and survival of patients. Taken together, our results identified GAS6-AS1 as a novel tumor suppressor in LUAD and unraveled its underlying molecular mechanism in reprogramming glucose metabolism. GAS6-AS1 potentially may serve as a prognostic marker and therapeutic target in LUAD.